Initial measurements of O‐ion and He‐ion decay rates observed from the Van Allen probes RBSPICE instrument. Issue 11 (5th November 2014) - Gerrard, Andrew; Lanzerotti, Louis; Gkioulidou, Matina; Mitchell, Donald; Manweiler, Jerry; Bortnik, Jacob; Keika, Kunihiro
Abstract H‐ion (∼45 keV to ∼600 keV), He‐ion (∼65 keV to ∼520 keV), and O‐ion (∼140 keV to ∼1130 keV) integral flux measurements, from the Radiation Belt Storm Probe Ion Composition Experiment (RBSPICE) instrument aboard the Van Allan Probes spacecraft B, are reported. These abundance data form a cohesive picture of ring current ions during the first 9 months of measurements. Furthermore, the data presented herein are used to show injection characteristics via the He‐ion/H‐ion abundance ratio and the O‐ion/H‐ion abundance ratio. Of unique interest to ring current dynamics are the spatial‐temporal decay characteristics of the two injected populations. We observe that He‐ions decay more quickly at lower L shells, on the order of ∼0.8 day at L shells of 3–4, and decay more slowly with higher L shell, on the order of ∼1.7 days at L shells of 5–6. Conversely, O‐ions decay very rapidly (∼1.5 h) across all L shells. The He‐ion decay time are consistent with previously measured and calculated lifetimes associated with charge exchange. The O‐ion decay time is much faster than predicted and is attributed to the inclusion of higher‐energy (> 500 keV) O‐ions in our decay rate estimation. We note that these measurements demonstrate a compelling need for calculation of high‐energy O‐ion loss rates, which have not been adequately studied in the literature to date.